Adubação fosfatada no crescimento inicial e na nutrição de mudas de pinhão-manso - Freiberger, Mariângela Brito [UNESP]; Guerrini, Iraê Amaral [UNESP]; Castoldi, Gustavo [UNESP]; Pivetta, Laerte Gustavo [UNESP] (Sociedade Brasileira de Ciência do Solo, 2014)
Physic nut (Jatropha curcas L.) is a perennial oilseed species that has aroused economic interest for biodiesel production. Among other factors, it is essential to determine the nutritional demands of this species to facilitate raising it as a crop. This study aimed to evaluate the early growth and mineral nutrition of physic nut, as well as soil fertility, as affected by phosphorus fertilization. The study was carried out in a plastic greenhouse in a completely randomized block experimental design with four replicates. The plants were grown in plastic pots filled with 50 dm³ of Latossolo Vermelho (Rhodic Hapludox). Application rates of 0, 50, 100, 150 and 200 mg dm-3 of P were tested, plus a control. Evaluations of plant height and root collar diameter were performed monthly. The experiment was ended 150 days after transplant of the seedlings, at which time leaf area, dry weight, leaf contents and total accumulation of macro- (N, P, K, Ca, Mg and S) and micronutrients (B, Cu, Fe, Mn and Zn) were performed, and soil chemical properties were analyzed. We concluded that absence of P fertilization alone is as limiting to early growth of physic nut as simultaneous absence of soil amendment and fertilization. The rate of 57 mg dm-3 of P may be recommended for initial growth of physic nut. The total accumulation of nutrients in physic nut seedlings exhibited the following order: K>N>Mg>Ca>P>S>Fe>Mn>B>Zn>Cu. Phosphorus fertilization resulted in increased soil cation exchange capacity (CEC).

O pinhão-manso (Jatropha curcas L.) é uma espécie oleaginosa perene que tem despertado interesse econômico para produção de biodiesel. A fim de viabilizar o cultivo dessa espécie, é fundamental determinar, entre outras coisas, as suas demandas nutricionais. Objetivou-se avaliar o crescimento inicial e a nutrição mineral do pinhão-manso, bem como a fertilidade do solo em razão da adubação fosfatada. O estudo foi desenvolvido sob estufa plástica, em delineamento experimental de blocos casualizados com quatro repetições. As plantas foram cultivadas em vasos plásticos preenchidos com 50 dm³ de um Latossolo Vermelho. Foram avaliadas as doses de 0, 50, 100, 150 e 200 mg dm-3 P, além de um tratamento-controle. Mensalmente, realizou-se a avaliação da altura e do diâmetro de colo das mudas. O estudo foi encerrado 150 dias após o transplantio das mudas, quando se determinaram a área foliar, a massa de matéria seca, os teores foliares e o acúmulo total de macro (N, P, K, Ca, Mg e S) e micronutrientes (B, Cu, Fe, Mn e Zn), além dos atributos químicos do solo. A ausência somente da adubação fosfatada é tão limitante ao crescimento inicial do pinhão-manso quanto a ausência simultânea da adubação e correção do solo. A dose de 57 mg dm-3 de P pode ser indicada para o crescimento inicial do pinhão-manso. O acúmulo total de nutrientes nas mudas de pinhão-manso apresentou a seguinte ordem: K>N>Mg>Ca>P>S>Fe>Mn>B>Zn>Cu. A adubação fosfatada promoveu aumento da capacidade de troca de cátions do solo (CTC).
Phosphorus fertilization on the early growth and nutrition of physic nut seedlings
Keywords: Jatropha curcas; área foliar; massa de matéria seca; macronutrientes; micronutrientes; Jatropha curcas; leaf area; dry matter; macronutrients; micronutrients